2022
DOI: 10.1038/s41419-022-05387-3
|View full text |Cite|
|
Sign up to set email alerts
|

Neurovascular injury associated non-apoptotic endothelial caspase-9 and astroglial caspase-9 mediate inflammation and contrast sensitivity decline

Abstract: Retinal neurovascular injuries are a leading cause of vision loss in young adults presenting unmet therapeutic needs. Neurovascular injuries damage homeostatic communication between endothelial, pericyte, glial, and neuronal cells through signaling pathways that remain to be established. To understand the mechanisms that contribute to neuronal death, we use a mouse model of retinal vein occlusion (RVO). Using this model, we previously discovered that after vascular damage, there was non-apoptotic activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The standard of care for RVO is therapy with injections of anti-VEGF. We have shown that targeting caspase-9 in a mouse model of RVO provides substantial morphologic, cellular and functional protection ( Avrutsky et al, 2020 ; Colon Ortiz et al, 2022 ). To compare the efficacy of inhibiting caspase-9, vs. blocking VEGF, mice were followed for 8 days following induction of RVO and treatment with either caspase-9 inhibitor eyedrops (Pen1-XBir3), or intravitreal injection of anti-VEGF antibody.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard of care for RVO is therapy with injections of anti-VEGF. We have shown that targeting caspase-9 in a mouse model of RVO provides substantial morphologic, cellular and functional protection ( Avrutsky et al, 2020 ; Colon Ortiz et al, 2022 ). To compare the efficacy of inhibiting caspase-9, vs. blocking VEGF, mice were followed for 8 days following induction of RVO and treatment with either caspase-9 inhibitor eyedrops (Pen1-XBir3), or intravitreal injection of anti-VEGF antibody.…”
Section: Resultsmentioning
confidence: 99%
“…This study represents a framework for comparing in vivo efficacy of experimental treatments against a clinically-established mechanism of action (VEGF-neutralization) in a mouse model of RVO. Our prior work has shown that non-apoptotic activation of caspase-9 regulates edema, gliosis and neuronal dysfunction in a well-defined mouse model of RVO (Avrutsky et al, 2020;Colon Ortiz et al, 2022). Here, Orthogonal measures capture different dimensions of RVO pathology in response to caspase-9 inhibition, VEGF-neutralization, or a combination treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cascade activation of multiple signaling pathways induced by excitotoxicity, oxidative stress, inflammation, and mitochondrial dysfunction is implicated in chronic cerebral under-perfusion, leading to immune cell recruitment and activation, and necrosis/apoptosis of vascular endothelial and supportive cells, as well as neurons [ 49 , 50 ]. Some of these mechanisms have been validated in the retina, offering novel therapeutic targets for RVO [ 6 , 17 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Venous recanalization initiates at 1 to 3 days after RVO, progressing to 2/3 to all individuals approximately a week later [3, 5-7, 9, 10, 15]. Some studies specified a 24-hour duration of venous occlusion, with subsequent venous recanalization no longer being considered an exclusion criterion [6,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%